Di (2-ethyl hexyl) phthalate (DEHP)-induced kidney injury in quail (Coturnix japonica) via inhibiting HSF1/HSF3-dependent heat shock response. (October 2018) - Li, Peng-Cheng; Li, Xue-Nan; Du, Zheng-Hai; Wang, Hui; Yu, Zhuo-Ran; Li, Jin-Long
Abstract: Di (2-ethyl hexyl) phthalate (DEHP) as a plasticizer can leach away from the plastic and hence entrances into the animal food chain which caused serious hazard in organs of animals, but there are few studies on DEHP kidney toxicity. The heat-shock response (HSR) consisting of the HSPs and HSFs plays an important role in various toxicity stress conditions. To investigate the influence on kidney toxicity and the modulation of HSR during DEHP exposure, female quail were fed the diet with 0, 250, 500 and 750 mg/kg DEHP by gavage administration for 45 days. The shrinkages of glomeruli and dilation of kidney tubule epithelia cells were observed in the kidney of DEHP-exposed quail. DEHP treatment could significantly decrease the expressions of HSP25, HSP27, HSP47, HSP60, while the expressions of HSP10, HSP40, HSP70, HSP90, HSP110 were upregulated in the kidney. In addition, the expression levels of HSF1 and HSF3 were significantly increased under DEHP. This is the first study to demonstrate quail exposure to DEHP is in fact detrimental to bird kidney. Besides, DEHP could attack HSR by affecting the synthesis of HSFs to mediate the transcription of the HSPs resulting in kidney damage. Graphical abstract: Di (2-ethyl hexyl) phthalate (DEHP) exposure induced the toxic effects of kidney and destroyed the pathophysiological integrity of the kidney in quail. Our findings provide evidence that DEHP-induced nephrotoxicity is associated with heat-shock response (HSR). DEHP exposure activated the HSR signaling pathway to prevent the toxicity in the kidney. Image 1 Highlights: DEHP exposure induced the renal injury in quail. DEHP-induced nephrotoxicity is associated with the modulation of HSFs and HSPs. DEHP exposure activated the HSR pathway responses in the kidney.